A numerical study on smoke back‐layering length in V‐shaped tunnels under natural ventilation. (25th March 2022) - Xie, En; Zhao, Wangda; Xu, Zhisheng; Zhang, Xiaochun; Xu, Weiku; Wang, Tianxiong; He, Lu
Summary: When a fire occurs at the lowest point of a V‐shaped tunnel, the stack effects on both sides have different directions and will compete with each other. The smoke back‐layering can be observed in the side with a smaller angle. In this work, the smoke back‐layering length in the V‐shaped tunnel was investigated by theoretical analyses and numerical simulations. The different inclination combinations of the V‐shaped tunnel and the heat release rates (HRRs) were concerned. The HRRs were set at 3, 5, 8, and 10 MW, respectively. An equivalent longitudinal velocity of the V‐shaped tunnel was proposed in this study. Different from the horizontal tunnel fire, the smoke back‐layering length decreased with the increase of the HRR in the V‐shaped tunnel due to the special smoke movement, and a prediction function was proposed to describe the relationship. After that, the effect of the different inclination combinations on the smoke back‐layering length was researched under the same HRR. The dimensionless smoke back‐layering length decreased with the rise of the sine difference between the two angles of the V‐shaped tunnel. In addition, when the smaller angle was fixed, the dimensionless smoke back‐layering length decreases logarithmically with the increase of the sine difference of the tunnel angles on both sides. At last, a semi‐empirical formula for smoke back‐layering length in V‐shaped tunnels was proposed.